Validation of the Questionnaire on Integration of Artificial Intelligence in Higher Education (Q-IAHE) - Vera, Fernando (Transformar, 2025)
The growing integration of Artificial Intelligence (AI) in higher education underscores the need for validated instruments to assess perceptions and practices related to its use. In Latin America, however, such tools are still limited. This study validates the Questionnaire on Integration of Artificial Intelligence in Higher Education (Q-IAHE). A pilot study was carried out with a Chilean sample (n = 53), followed by a broader validation with a Mexican sample (n = 359). Analyses confirmed strong internal consistency (Cronbach’s alpha = .898) and a stable factorial structure across both groups, identifying four main dimensions of AI integration in learning and teaching. The results demonstrate that the Q-IAHE is a reliable and valid instrument for exploring AI adoption in higher education. Its application offers valuable insights for international research on educational innovation, pedagogy and digital transformation.